Peran Mahkamah Konstitusi dalam Menjaga Prinsip Konstitusionalisme di Indonesia: Studi Putusan Judicial Review Tahun 2019–2024 - Amin, Fakhry (Dinasti Research, 2025)
The Constitutional Court holds a strategic position as the guardian of the constitution in the Indonesian state system. One of the main instruments for carrying out this role is the authority of judicial review of the 1945 Constitution of the Republic of Indonesia. This study aims to analyze the extent to which the Constitutional Court has carried out its function of safeguarding constitutionalism through judicial review decisions during the period 2019 to 2024. This study uses a juridical-normative approach by analyzing the legal norms contained in the constitution and various relevant Constitutional Court decisions. The results show that the Constitutional Court has demonstrated a commitment to the principles of constitutionalism, despite some dynamics and controversies in its practice in interpreting the constitution. This study emphasizes the importance of the Constitutional Court's consistency and courage in maintaining the supremacy of the constitution amidst political and social pressures.